Religious Dialectics in Urban Society in Tolerance Villages of Bandung City: Analysis of Emil Durkheim's Religious Functionalism - Hidayatulloh, Taufik; Saumantri, Theguh (Al-madinah: Journal of Islamic Civilization, 2024)
Religion plays a significant role in the social life of humans. Its function is not limited to the individual's spiritual aspects but also encompasses broader social dimensions, including the formation of communal identity, social solidarity, and societal stability. This study aims to explore the dialectics of religion in the urban community of Tolerance Village in Bandung through the perspective of Emil Durkheim's functionalism of religion. The research employs a qualitative approach with a descriptive-critical method. The results indicate that religious practices in Tolerance Village serve not only as a personal expression of an individual's relationship with God but also as a means to build communal identity and strengthen social solidarity. Functionalism of religion, within the context of religious dialectics, fosters harmony and religious teachings interpreted contextually can create inclusive and tolerant religious practices, in accordance with local culture and the needs of urban society. This study's findings are expected to serve as a reference for further research in specific religious phenomena and religious studies in general.